False Passage to the Trachea after Emergency Intubation in a Victim of Near Hanging. (15th May 2013) - Pourmand, Ali; Shokoohi, Hamid
Abstract : Emergency medicine physicians should have enough knowledge and experience to deal with emergent and traumatic difficult airway. In this paper, we present a case of near hanging with neck soft tissue injury, tracheal and esophageal rupture that is complicated by a displaced intubation and false passage to the trachea.